Arus Kas, Laba Akuntansi, Profitabilitas, Ukuran Perusahaan, dan Return Saham Pada Perusahaan Sektor Kesehatan - Fauziah, Dien Ajeng; Devi, Fitriyah Kusuma; Rachmawati, Afiah Ning (Asosiasi Dosen Akuntansi Indonesia, 2024)
This study aimed to ascertain the impact of cash flow, accounting profit, profitability, and company size on stock returns in health sector companies listed on the IDX between 2018 and 2022. This type of research is quantitative and employs a causal associative approach. The research sample was selected through a purposive sampling method, resulting in the inclusion of 40 samples. The data source was secondary data, with data collection methods including documentation and online data. The data sources were obtained from the official IDX website. The results indicated that accounting profit and profitability significantly influence stock returns, whereas cash flow and company size do not. Furthermore, accounting profit, cash flow, profitability, and company size significantly influence stock returns simultaneously. Accounting profit exerts the most dominant influence on stock returns